Nagham Al-Quran dalam Masyarakat Bima - Muhammad Aminullah (Proceedings of Annual Conference for Muslim Scholars, 2017)
Reading and understanding the Quran is the command of Allah and Propeth. To implementing that command, humans are required to know, develop and preserve it. Nagham al-Qur’an known as the art of reading the Quran is implementing of that command. In the case, Muslim in Bima develop nagham al-Qur’an in everyday life, both individually and social interaction. This is that makes nagham al-Qur’an as one of Islamic tradition and culture that is very demand by society of Bima. Implementing nagham al-Qur’an that is do by society of Bima can be seen in some activities, that is : nagham al-Qur’an as opener reading in events, tadarus al-Qur’an, and haflah tilawah al-Qur’an. The Quran in society of Bima have formed Muslim personal doing command of Allah and the Quran both individually and social interaction. It can be seen positive response from society of bima to nagham al-Qur’an in thse activies.Keyword: Nagham al-Qur’an, Tradition, Society, Bima